Are parental sociodemographic factors, oral health knowledge and practices linked to the oral health habits of their children with cleft lip and palate? - Dilan Altun; Sevilay Karahan; Fatma Figen Özgür; Meryem Uzamış Tekçiçek; Melek Dilek Turgut (Medical Journals Sweden, 2024)
Objective: Children with cleft lip and palate (CLP) have a greater risk of dental caries. The parents' knowledge and attitudes may have an impact on their children's oral health and dietary habits. Therefore, the aim of this study was to assess the socio-demographic characteristics, oral health knowledge, oral health behaviours, and habits of the parents in addition to the relationship with the oral health and dietary practices of their children with CLP. Material and methods: The parents of 343 patients with CLP participated in the study. An online questionnaire with 52 questions regarding sociodemographic characteristics, oral health and oral hygiene practices was presented to them. Results: Parents with higher level of education had better oral health knowledge (p < 0.05). Logistic regression analysis showed that the factors affecting the child's tooth brushing habits were the mother's age (odds ratio [OR] = 1.071, 95% confidence interval [CI]: 1.062-1.153), the father's employment status (OR = 2.089, 95%CI: 1.065-4.097), and the mother's last dental visit (OR = 1.995, 95%CI: 1.119-3.557). The factors affecting the child's toothpaste usage were the mother's age (OR = 1.106, 95%CI: 1.030-1.114), the father's employment status (OR = 2.124, 95%CI: 1.036-4.354), and the mother's last dental visit (OR = 2.076, 95%CI: 1.137-3.79). Conclusions: Parental factors have a significant influence on the oral health-related behaviours of children with CLP.